Exploring the Influence of Earnings Management on the Value Relevance of Financial Statements: Evidence from the Bucharest Stock Exchange - Georgiana Burlacu; Ioan-Bogdan Robu; Ionela Munteanu (International Journal of Financial Studies)
Although financial statements are extremely important to investors in decision-making processes, their reliability can be affected by earnings management (EM) practices, which involve manipulating financial reports in order to achieve managerial benefits. This study explores the relationship between earnings management and firm valuation, based on accounting information’s predictive value, specifically investigating how EM influences the value relevance (VR) of earnings on share price. The research focuses on a sample of audited companies listed on the Bucharest Stock Exchange (BSE) between 2019 and 2021, comprising 62 entities. Using regression analysis, we explored the importance of accounting information for investors following Ohlson’s research and examined the relationship between EM and VR based on Jones’s model. The findings indicate that earnings significantly impact stock prices, highlighting their value relevance in the Romanian stock market. However, the practice of earnings management reduces the value relevance of earnings because it decreases the reliability of the accounting information. The main contribution of this analysis is to provide a fresh perspective on earnings management (EM) within the BVB framework by highlighting its pivotal role in shaping the motivation and behavior of corporate managers.